Synchronized scheduling of air transportation and assembly manufacturing in consumer electronics supply chain - Li, Kunpeng (2008)
The consumer electronics has been a booming industry in recent years. Motivated by the challenges confronted by a major PC manufacturer in consumer electronics industry, this research studies the problem of synchronizing the assembly manufacturing and the air transportation to achieve accurate delivery with minimized delivery cost. There are two integrated decisions involved in the research problem that determine: (1) proper allocation of orders to various available flights in the planning period (2) an appropriate release time for each order in assembly ensuring it can catch the allocated flight after assembly, and to minimize the waiting time between assembly and air transportation.